Perancangan Sistem Informasi Formulir Waktu Penyediaan Dokumen Rekam Medis Rawat Inap Menggunakan Visual Studio 2010 - Jonda Eka Permana; Erix Gunawan; Falaah Abdussalaam (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The activity of receiving inpatients at a hospital must record the patient's arrival time until the medical record documentation is available or you could say until the patient goes home. So that the time of admission of inpatients is in accordance with the standard or not. This activity is still done manually (paperless) which is often a hassle for registration officers and prone to data manipulation. The purpose of this study is to create an information system for inpatient admission time efficiency forms to provide information related to patient admission times electronically that makes it easier for registration officers to input data or the time when patients arrive until medical record documents are available, reduce costs and minimize data manipulation. . The creation of an information system for the time efficiency of inpatient admissions uses data collection methods by conducting interviews, reviewing the literature, and observing. The system design method uses ERD (entity relation diagram) and DFD (data flow diagram) then implemented with Microsoft Visual Studio 2010 programming language.